2022
DOI: 10.1177/0734371x211065349
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Employer Attractiveness of Public Sector Organizations to Nonprofit and Private Sector Organizations: An Experimental Study in Germany and the U.S.

Abstract: Sector preferences in job choice have rarely been tested empirically across different administrative systems. We address this gap and apply a between-subject experimental design to examine the attractiveness of public, private, and nonprofit employers in two countries in different administrative traditions. Respondents ( n = 362) from an Anglo-Saxon (i.e., the U.S.) and continental European country (i.e., Germany) were exposed to job advertisements that only differed in the employer’s sector affiliation, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
1
22
0
Order By: Relevance
“…Therefore, the results are in line with Berthon et al (2005), that is, all dimensions of employer branding interest value (level of attraction of a potential employee to an organisation); social value (related to a pleasant and relaxed work environment); economic value (linked to economic issues, such as above-average salary); development value (employee appreciation) and application value (employee opportunity to apply their knowledge in an organisational context), seem to count towards attracting candidates to an organisation. Recently, Cordes and Vogel (2022) demonstrated that employer branding was related to the attractiveness of applicants towards a job and influenced their decision. Kashyap and Verma (2018) also showed that employer branding predicted not only the decision to apply for a job offer but also reduced turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results are in line with Berthon et al (2005), that is, all dimensions of employer branding interest value (level of attraction of a potential employee to an organisation); social value (related to a pleasant and relaxed work environment); economic value (linked to economic issues, such as above-average salary); development value (employee appreciation) and application value (employee opportunity to apply their knowledge in an organisational context), seem to count towards attracting candidates to an organisation. Recently, Cordes and Vogel (2022) demonstrated that employer branding was related to the attractiveness of applicants towards a job and influenced their decision. Kashyap and Verma (2018) also showed that employer branding predicted not only the decision to apply for a job offer but also reduced turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Erlinda and Safitri (2020) showed that employer branding and organisational attractiveness were antecedents of intentions to apply for job offers. Additionally, Cordes and Vogel (2022) demonstrated that the social and organisational representation of an employer explained why employer branding influenced the decision of an applicant to apply for a job. Similarly, Santiago (2019) demonstrated that, for millennials, employer branding strategies tended to ameliorate the image of an employer, which resulted in higher motivation to apply for a job offer in that organisation.…”
Section: Discussionmentioning
confidence: 99%
“…The very little natural green space that the region offers to its inhabitants and the local depletion of biodiversity may dissuade some public agents from coming or staying. Since the 2000s, the creation of green spaces has slowed down while the region's population has been steadily increasing (Conseil Régional d'Île-de-France, 2017 [120]). Half of Île-de-France residents live in areas with less than 10 m² of green and wooded areas per capita, the minimum threshold recommended by the World Health Organisation (WHO).…”
Section: Challengesmentioning
confidence: 99%
“…However, the denser the urban context in which the inhabitants live, the more they need easily accessible green spaces. However, certain developments are encouraging signs: the development of organic farming, renewable energy and waste recycling, and the recognition by the Region of the importance of a green heritage for the well-being and attractiveness of the territory (Conseil Régional d'Île-de-France, 2017 [120]).…”
Section: Challengesmentioning
confidence: 99%
“…This can result in consistency in the training programs, leading to varying employee skills and knowledge levels. HR management training approaches to sustainable public service administration can be challenging due to limited resources, cultural and language differences, resistance to change, little understanding of sustainable public service administration, and lack of coordination among different public service organizations (Cordes & Vogel, 2022).…”
Section: Introductionmentioning
confidence: 99%